1992
DOI: 10.1007/bf03222748
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additives on zinc deposited from zinc sulfate solutions

Abstract: Zinc is industrially electrowon from acid zinc sulfate solutions at ambient temperatures. Some refiningagents are usually added to improve the deposit qualities. Gelatin is a traditional additive, but other additives are also used. In the investigation described here, the basic parameters of deposition (e.g., current density, acid concentration, and zinc concentration) were optimized. Gelatin and a tetraalkylammonium salt (T AS) were used separately and in combination as grain refiners of the cathodic deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It is suggested that the electric field provides electrophoretic motion of charged gelatin to the cathode surface and zinc deposition is influenced by the adsorbed gelatin. The observed changes in deposit microstructure can result from increases in the cathode overpotential arising from gelatin adsorption (Afifi et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the electric field provides electrophoretic motion of charged gelatin to the cathode surface and zinc deposition is influenced by the adsorbed gelatin. The observed changes in deposit microstructure can result from increases in the cathode overpotential arising from gelatin adsorption (Afifi et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, it is difficult to stabilize particles in solutions of metal salts due to their high ionic concentration (Biest and Vandeperre, 1999). It has been suggested that gelatin was protonated and positively charged (Afifi et al, 1992) in the acidic environment. The protonated gelatin macromolecules then adsorbed on the ceramic particle surfaces promoting electrosteric stabilization of the ceramic particles, which is less sensitive to high ionic concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, all these compounds are common additives for zinc electroplating. [20][21][22][23][24][25][26][27][28][29][30] The following results attempted gradually to show their effect and coeffect on the preparation of nanocrystalline zinc coatings on steel specimens. By the way, a small amount of ethanol or methanol was generally used to dissolve BA in aqueous solutions, 27,28 but the pre-experiments found that these two compounds did not dissolve BA fully in the base solution S 0 , mainly due to the high concentration of zinc sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…Organic molecules such as animal-derived glues, gelatin, and gums are widely used in the industry [28,29]. They act in zinc electrodeposition mainly as dendrite inhibitors, grain refiners, and brighteners [31,32]. Gelatin (G) and gum arabic (GA) have also been widely used as dispersants, namely, to avoid the agglomeration of inert particles in aqueous solutions [27,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%